Discrimination of organic acids using a three molecule array based upon cruciform fluorophores - Davey, Evan; Zucchero, Anthony J.; Trapp, Oliver; Bunz, Uwe H. F. (Journal of the American Chemical Society, 2011)
A small array was obtained from three reactive cruciform fluorophores in six different solvents. The array discerned 10 different aromatic carboxylic acids by protonation-induced fluorescence shifts, which were recorded by digital photography. This simple array can discern acids that have closely spaced pKa values.
Gesehen am 29.04.2022